A case of catastrophic antiphospholipid syndrome, which presented an acute interstitial pneumonia-like image on chest CT scan. Issue 1 (January 2015) - Kameda, Tomohiro; Dobashi, Hiroaki; Susaki, Kentaro; Danjo, Junichi; Nakashima, Shusaku; Shimada, Hiromi; Izumikawa, Miharu; Takeuchi, Yohei; Mitsunaka, Hiroki; Bandoh, Shuji; Imataki, Osamu; Nose, Masato; et al.
Abstract We report the case of catastrophic antiphospholipid syndrome (CAPS) complicated with mixed connective tissue disease (MCTD). A female patient was diagnosed with acute interstitial pneumonia (AIP) with MCTD by chest CT scan. Corticosteroid therapy was refractory for lung involvement, and she died due to acute respiratory failure. The autopsy revealed that AIP was compatible with lung involvement of CAPS. We therefore suggest that chest CT might reveal AIP-like findings in CAPS patients whose condition is complicated with pulmonary manifestations.